Social Work Crime as an Alternative to Resolving Overcrowding in Correctional Institutions - Kholdaa, Madya Cinta; Pujiyono, Pujiyono (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Overcrowded in correctional facilities results from various factors, including increased inmate numbers due to prevailing prison sentencing policies, judicial inefficiencies in handling detainees, and high recidivism rates. The consequences of overcrowding are severe, impacting the ability to meet inmates' basic needs, leading to poor sanitation and health conditions, and reducing the effectiveness of rehabilitation programs. Social work penalties, adopted in several countries, offer a rehabilitative approach that focuses on social reintegration rather than isolation through prison sentences. These penalties help facilitate inmate recovery by involving them in beneficial community activities such as environmental care or social services. This research employs a normative juridical methodology, utilizing document analysis of relevant legal and literature sources. Data are qualitatively analyzed, considering legislative regulations, legal literature, and related research findings. The study aims to contribute to more effective policy formulation for managing overcrowding in correctional facilities and to consider more humane and rehabilitative sentencing alternatives